The Impact of Osteoporosis on Teeth Decay in relation to Salivary Vitamin D among Menopause in Baghdad city, Iraq - Hameed, Zainab Abdulkareem; Radhi, Nada Jafer MH (AL-Kindy College Medical Journal, 2023)
Background: Osteoporosis is a systemic skeletal disorder that has an impact on general health, dental health and salivary composition. The mineralization of teeth happens simultaneously with that of the skeleton, but if mineral metabolism is disrupted, tooth failures will resemble those that affect bone tissue. Vitamin D plays a key role in bone and tooth mineralization. Objective: to evaluate the impact of osteoporosis on teeth decay in relation to salivary vitamin D among menopause in Baghdad city. Subjects and Methods: This study was cross sectional study. The study group consists of 45 menopausal women with osteoporotic disease as appeared in dual energy X-ray absorptiometry (DEXA) scan. The control group consists of 45 menopausal women without osteoporosis as appeared in (DEXA) scan. Dental caries was examined according to WHO (2013). Biochemical salivary analysis made for vitamin D. Statistical Analysis of the data were carried out using SPSS version 21. Results: The percentage of dental caries occurrence was 100% among groups. Results revealed that DMFT value was higher but statistically not significant among osteoporotic women. Concerning DMFS components, the data showed that DS, MS and FS was higher among study group but statistically not significant. Salivary vitamin D is lower in study group with significant difference. Conclusion: The caries experience was higher in osteoporotic women and missing teeth were reported to be most common in both groups. Salivary vitamin D is lower in osteoporotic group. Therefor old adult women need special oral health preventive and educational programs.